Awareness of lifestyle modification in females diagnosed with polycystic ovarian syndrome in India: explorative study - Pitchai, Pothiraj; Sreeraj, S. R.; Anil, Parmar Reema (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Background: Polycystic ovarian syndrome (PCOS) adversely affect women at varying stages of their life and imperative to emphasis on prevention strategies since incidence of PCOS is on the rise. Study aims to explore perception on PCOS, awareness on life style modification, emotional attributes, concern regarding PCOS and utilization of physiotherapy services. Methods: The study was conducted in Mumbai and Navi Mumbai, India. Self-made validated questionnaire was administered. Descriptive analysis was done. Perception on PCOS, lifestyle modification, emotional attribution and biggest concern were calculated as absolute frequencies and were reported as overall percentages. Chi square test was applied on the demographic factor’s influence on level of awareness. Results: 21% of the respondents are very well aware about PCOS. 51% reported as doctor was their main source of information about PCOS. 81% expressed that PCOS is manageable one. 62% aware that exercise helps in the management of PCOS. Out of this, 39% are doing exercise on a regular basis. However all the study participants reported, they have not had any consultation from physiotherapist for their structured exercise program.32% attributed to anxiety after the diagnosis of PCOS. 64% of the respondents aware that changing in diet or eating habits can influence in PCOS. However 95% of the subjects concurred to follow life style modification. Conclusions: Efforts need to intensify in creating awareness on the general public about PCOS. Absolute majority of the study participant uncoerced to follow lifestyle modification however emphasis needs to address on multidisciplinary approach in managing PCOS.